CALL FOR PAPERS--------------------------->>DOWNLOAD THE BROCHURE - -, - (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
The Next edition of eJIR will be published in January 2021. The deadline for submission is November 29, 2020. Please download the brochure----------->